Perceptions and expectations of college students about the Internet of Things - Vasconcelos, C. (2019)
The Internet is increasingly used as a means of communication of excellence. With the increasing ease and access to virtual communication, namely through social networks, it is verified that the relationships between people have assumed new forms of expression and higher levels of importance in society. In addition to communication between people, there is also an increasing possibility of any object communicating and connecting to other objects, with a unique way of identifying, anywhere, with devices connected to the Internet, this being the essential concept of Internet of Things (IoT). In this paper, our main goal is understand how college students represent IoT and what are their perceptions and expectations about it. From their point of view, is important to verify what is the impact that IoT may have on their personal lives, academic performance and in society. According to the methodology adopted we performed individual interviews with a population of college students. Data were processed through context analyses, after being transcribed and analyzed, using a typical software - Leximancer. Our findings showed that, in general, participants have an accurate perception about the Internet of Things, and how it works, and that they also have positive expectations in relation to it, considering it can be useful to our day-to-day life. Although, at the same time, they highlight the importance of being careful in terms of privacy, threats, vulnerabilities and risks associated to the internet.